The killing machine: an approach to the relationship between the legal system and the subject through the literary intertext - Falconí, Diego (Iuris Dictio, 2013)
This paper aims to link -through the intertextual methodology- Literature and Law. By binding these two traditions it is possible to address a problematic issue: the way the legal system disciplines the human body. In this essay a comparative analysis between Philosophy and Political Theory articulates a theoretical framework, which criticizes -from the perspective of the Humanities and its focus on the human body- the notion of machinery, present in several assumptions of nineteenth-century legal positivism. This framework gives a key to reinterpret three different literary texts, written in diverse spaces and times: "In the Penal Colony", by Franz Kafka, The future Eve, by Villiers de L’Isle Adam, and “Del seguro contra robos de autos" (Divertinventos), by Abdón Ubidia.